STRATEGI PENGEMBANGAN USAHA MENGGUNAKAN METODE SWOT DAN BOSTON CONSULTING GROUP MATRIX - Sabaya, Zilva Abd. Rahim; Lasalewo, Triandi; Uloli, Hendra (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2023)
This study aims to identify internal and external environmental factors and to determine the position of CV. XYZ on the level of growth and market share and determine the best business development strategy to win market share competition. The method used in this study to identify internal and external factors that exist in CV. XYZ, namely by using the SWOT (Strength, Weakness, Opportunity, Threats) method and to determine market growth and market share in CV. XYZ uses the BCG Matrix (Boston Consulting Group Matrix) method. In this study, the authors used a descriptive quantitative approach by identifying external and internal factors as well as sales data in the last 2 years that could influence business development at CV. XYZ. The conclusion of this research is CV. XYZ is in quadrant 1 which is obtained from external and internal results which have been processed later on the BCG PT method. XYZ is in the cash cow quadrant which means CV. XYZ experienced low market growth and high relative market share. Advice to the company is to do business development and get certified.